THE QUALITY OF THE EDUCATIONAL PROCESS IN THE UNIVERSITY THROUGH STUDENTS’ EYES - S. S. Kotova; I. I. Hasanova (Образование и наука)
The aim of the article is to describe and analyse the basic requirements and expectations of consumers of educational services, which the educationa organization during the planning and implementation of the activities shouldbe guided by.Methods. The methods involve theoretical and empirical data collection, methods of mathematical statistics, methods of descriptive statistics; analysis of legislative and regulatory documents; comparison and synthesis of the findings of research scientists on the quality of an educational process; psycho-pedagogical observation,  uestionnaire study; studying of experience of a quality evaluation of the services provided by higher educational organizations on the part of consumers.Results and scientific novelty. The definitions of the concepts of «quality of higher education» and «consumer monitoring» are given. The most significant trends of consumer monitoring are considered: monitoring of indicators related to external consumers (applicants, students, parents, employers); monitoring of a teaching quality and indicators that reflect the level of development by students of educational programs. The questionnaire for studying of real degree of a consumer satisfaction(students) by quality of educational services at the Russian Vocational Pedagogical University is worked out and approved. The results of the questionnaire are presented. 1–4 year students of full-time education at the Russian Vocational PedagogicalUniversity, in total – 36 groups take part in the questionnaire. The amountof selection – 575 respondents; information data processing was performed using methods of the content analysis and correlation analysis Practical significance. The conducted research allowed us to concretize the requirements and consumer expectations of educational services, to develop and implement a road map aimed at improving the quality of university education services.